Malaysian high schoolers’ reading literacy performance: Trends and patterns across states - Ganasan, Marcia Jane; Razak, Nordin Abd.; Jamal, Marlina (Universitas Pendidikan Indonesia, 2020)
Reading literacy is often understood as a basic skill, and it is gaining recognition as the most functional means to educational attainment and individual development. It not only sets a benchmark but also reveals students’ strengths and weaknesses through performance measurement. This paper attempts to investigate sixteen-year-olds’ reading literacy proficiency using a performance band system in reporting their ‘can’s and ‘cant’s in reading. It drew insights from the Text-Task Respondent Theory of Functional Literacy (White, 2011) and the Revised Bloom’s Taxonomy (Anderson Krathwohl, 2001), where pertinent concepts were drawn to address students’ functional abilities. The study involved a total of 813 sixteen-year-old students representing the northern, southern, central, and east coast regions of Peninsular Malaysia (Penang, Perak, Perlis, Selangor, Kedah, Kelantan, Terengganu, and Johor). A survey research method was employed to capture cognitive competencies that denoted students’ functional abilities when it came to reading literacy. The study measured the students’ reading literacy attainment based on a proficiency scale spanning on five-band levels. The findings of the present study revealed that the majority of the students attained Band 3, where they demonstrated a moderate understanding of texts and were able to integrate some part of texts to infer meaning. The study provides valuable insights to policymakers, educationists, employers in making data-driven decisions to improve educational outcomes. It also attempts to shed some light on the current pedagogical trends and provide suggestive practices in reading.